Pengungkapan Internet Financial Reporting Berdasarkan Reputasi Auditor dan Profitabilitas - Iin Rosini; Dani Rahman Hakim (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2020)
This study aims to analyze the disclosure of internet financial reporting (IFR) based on auditors' reputation and profitability. Data panels with purposive sampling methodology are used to collecting the 204 total samples from 51 manufacturing companies whose listed on Indonesia Stock Exchange from the 2016 to 2019 period. By using the data panel regression random effect model, this study reveals that an auditor’s reputation has a positive effect on IFR. This study also finds evidence that profitability which is proxied by return on assets (ROA) has a positive effect on IFR. This study contributes to the literature especially in using the random effect regression data panel model which has been widely found in the context of Indonesian studies. This study implies the need for Indonesia’s government through the Financial Services Authority (OJK) to encourage companies to use reputable auditor services. Besides, future research is expected to use other independent variables such as the audit committee, auditor professionalism, and the company's financial characteristics in influencing IFR disclosure.